High-Performance Parallel Database Processing and Grid Databases - Taniar, David (John Wiley & Sons, 2011)
This book targets the theoretical/conceptual details needed to form a base of understanding and then delivers information on development, implementations, and analytical modeling of parallel databases. It includes key information on new developments with grid databases. Also uses a theoretical and practical balance to support in-depth study of parallel query processing offered by modern DBMS as well as hands on experience of parallel query algorithms development, implementation, and analysis.